Not always for richer or poorer: The effects of income shocks and house price changes on marital dissolution - Harminder Battu; Heather Brown; Miguel Costa-Gomes (European Regional Science Association (ERSA), 2013)
There has been much informal speculation on how changes in economic circumstances contribute to partnership dissolution; however there has been little empirical work testing these speculations. This paper aims to shed light on how micro level factors such as receiving a financial windfall and changes in investment income as well as macro level changes such as changes in house prices at the regional level impact on the likelihood of divorce. We use information from 18 waves (1991-2008) of the British Household Panel Survey. The long panel allows us to control for both upturns and downturns in the economic cycle. The estimation strategy employs a discrete time duration model. The results suggest that windfalls and changes in investment income may be pathways through which financial surprises or new information impacts on the likelihood of partnership dissolution. Specifically we find a positive and significant effect on partnership dissolution of a wife receiving an inheritance and a husband having a positive change in his income from interests and dividends. This finding is consistent with much of the theoretical literature suggesting a positive shock will reduce the benefits of the current marriage and increase the likelihood of an individual finding a ?better? partner. Interaction models for changes in regional house prices and housing tenure show a small positive significant increase in the likelihood of divorce for couples in mortgaged property and private rented accommodation when house prices rise by 1% compared to those in social housing. A rise in house prices for couples with mortgages may increase the pay-offs for divorce reducing the returns to remaining in the current partnership. For couples, in private rented accommodation, a rise in house prices may signify an inability to get on the housing ladder reducing the benefits of the current partnership leading individuals to seek a partner with more capital or a homeowner.
Keywords: J61; R23; 330; Housing; Homeownership; Labour markets; Marital Status